2017
DOI: 10.5505/agri.2017.67984
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Analgesia after Arthroscopic Shoulder Surgery: A Comparison of Single Shot Interscalene Block with Single Shot Supraclavicular Block

Abstract: SummaryObjectives: In arthroscopic rotator cuff surgery for postoperative analgesia opioids, nonsteroid analgesics, and local anesthetics can be used. This study aimed to compare the effectiveness, additional analgesic requirements, patients satisfaction, and complications of single-shot interscalene and supraclavicular blocks. Methods: After obtaining the ethics committee's approval and informed consent, 50 ASA I-II patients were randomized to either the interscalene (GISB) or supraclavicular (GSCB) group. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…This technique advantageously numbs the branches of the suprascapular nerve, which supplies up to two-thirds (70%) of the sensory input to the glenohumeral joint, including the supraspinatus and infraspinatus muscles. According to this anatomical foundation, this technique has been advocated to provide adequate pain control, including equivalent analgesic effects to IBPB (30) during shoulder surgery (16). A recent RCT by Sayed et al showed that the addition of suprascapular nerve block to intraarticular injection of steroids or hyaluronic acid resulted in enhanced analgesic effects among patients with adhesive capsulitis of the shoulder (31).…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…This technique advantageously numbs the branches of the suprascapular nerve, which supplies up to two-thirds (70%) of the sensory input to the glenohumeral joint, including the supraspinatus and infraspinatus muscles. According to this anatomical foundation, this technique has been advocated to provide adequate pain control, including equivalent analgesic effects to IBPB (30) during shoulder surgery (16). A recent RCT by Sayed et al showed that the addition of suprascapular nerve block to intraarticular injection of steroids or hyaluronic acid resulted in enhanced analgesic effects among patients with adhesive capsulitis of the shoulder (31).…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…Since January 2017, 16 RCTs have investigated diaphragm-sparing nerve blocks for shoulder surgery14–29 (see online supplementary table 1 and figure 1). Overall, the quality of the trials was high (median Jadad score=3.5).…”
Section: Evidence Derived From Rcts Published Between January 2017 Anmentioning
confidence: 99%
“…Supraclavicular block constitutes the most investigated alternative to ISB since 2017 (seven RCTs) 16–22. The majority of trials suggest that, compared with ISB, supraclavicular blocks result in similar pain control, breakthrough analgesic consumption and patient satisfaction 16–18 21 22.…”
Section: Evidence Derived From Rcts Published Between January 2017 Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite optimal postoperative pain management and patient satisfaction, cliniciansʹ risk of postoperative complications is still an important challenge. Many studies have been conducted to reveal which method is superior in postoperative pain control after arthroscopic rotator cuff operations (6,10,(16)(17)(18)(19). However, although the blocks performed at the surgical site and general anesthesia in shoulder arthroscopy are known to be safe, easy, and have lesser ÖZ Amaç: Cerrahi sonrası özellikle ilk 48 saatte görülen postoperatif ağrı önemli bir problemdir ve postoperatif ağrı kontrolünde çeşitli yöntemler kullanılmaktadır.…”
mentioning
confidence: 99%